2016
DOI: 10.1016/j.jcrysgro.2016.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and effects of impurities in different growth zones within basic ammonothermal GaN

Abstract: The ammonothermal method is one of the most promising candidates for large-scale bulk GaN growth due to its scalability and high crystalline quality. However, emphasis needs to be put on understanding the incorporation and effects of impurities during growth. This article discusses how impurities are incorporated in different growth zones in basic ammonothermal GaN, and how they affect the structural, electrical and optical properties of the grown crystal. The influence of growth time on the impurity incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…[26,[34][35][36] Ammonothermal GaN substrates have been used in homoepitaxy [35,37,38] and as substrates for InGaN LDs. [39] Although the crystalline quality of ammonothermal GaN is very high, recent studies have shown that the high concentration of impurities [22,40,41] and native point defects [42][43][44] in the as-grown material have a significant effect on the material properties. The most dominant impurities, oxygen and transition metals, cause absorption in the visible region [23,42] and their non-uniform incorporation in the growing crystal can cause build-up of strain.…”
Section: Progress Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…[26,[34][35][36] Ammonothermal GaN substrates have been used in homoepitaxy [35,37,38] and as substrates for InGaN LDs. [39] Although the crystalline quality of ammonothermal GaN is very high, recent studies have shown that the high concentration of impurities [22,40,41] and native point defects [42][43][44] in the as-grown material have a significant effect on the material properties. The most dominant impurities, oxygen and transition metals, cause absorption in the visible region [23,42] and their non-uniform incorporation in the growing crystal can cause build-up of strain.…”
Section: Progress Reportmentioning
confidence: 99%
“…The most dominant impurities, oxygen and transition metals, cause absorption in the visible region [23,42] and their non-uniform incorporation in the growing crystal can cause build-up of strain. [31,40] optical absorption [42] and compensation doping. [43] Additionally, the formation of helical dislocations during heat treatment and epitaxy process has very recently been reported and associated with interaction of dislocations and point defects.…”
Section: Progress Reportmentioning
confidence: 99%
See 3 more Smart Citations